Procedural simplification in mitral valve transcatheter edge-to-edge repair: full echocardiographic guidance and outcomes - Jianrui Ma; Peijian Wei; Fengwen Zhang; Junke Chang; Manchen Gao; Chuangshi Wang; Xiaofang Yan; Cheng Wang; Shouzheng Wang; Yongquan Xie; Fang Fang; Xiangbin Pan (International Journal of Cardiology: Heart & Vasculature)
Background: Our group pioneered attempts to simplify the mitral valve transcatheter edge-to-edge repair (M-TEER) procedure under full echocardiographic guidance; however, its safety and effectiveness remain unclear. This study aimed to compare its outcome with the traditional procedure under echocardiographic and fluoroscopic co-guidance. Methods: From Jan 2021 to May 2024, 194 mitral regurgitation (MR) patients undergoing the simplified procedure (Echo guidance group, n = 113) and the traditional procedure (Co-guidance group, n = 81) were retrospectively reviewed. The propensity score matching (PSM) method was performed as a sensitivity analysis. Results: As defined by Mitral Valve Academic Research Consortium, the 30-day major adverse events, technical success, device success, and procedural success in the Echo guidance group were 5.31 %, 97.3 %, 89.4 %, and 88.5 %, similar to 8.64 %, 96.3 %, 85.2 %, and 84.0 % in the Co-guidance group, respectively (p > 0.05). Significant MR reduction and improvements in New York Heart Association functional class were observed in both groups (p < 0.05). The 1-year freedom from all-cause mortality and a composite of all-cause mortality and heart failure hospitalization were 94.5 % (95 % confidence interval (CI), 89.8 %–99.4 %) and 90.1 % (95 % CI, 83.6 %–97.2 %) in the Echo guidance group, similar to 92.1 % (95 % CI, 86.3 %–98.4 %) and 88.4 % (95 % CI, 81.6 %–95.9 %) in the Co-guidance group, respectively (p > 0.05). PSM-cohort analysis confirmed these findings. Conclusions: The simplified M-TEER procedure under full echocardiographic guidance showed comparable outcomes to the traditional procedure under echocardiographic and fluoroscopic co-guidance.